Septic arthritis of the temporomandibular joint leading to an epidural abscess - Wittig, Joern (BMJ Case Rep, 2018)
Septic arthritis of the temporomandibular joint (TMJ) is rare, but patients with this diagnosis are at high risk for significant morbidity. We present a case of a 15-year-old man who presented with increasing trismus for 3 days. He had only minimal discomfort and swelling of the right cheek and temporal region, and pericoronitis of an impacted wisdom tooth was suspected. Under intravenous antibiotics, pain subsided, but trismus and a slight swelling remained. CT scan showed septic arthritis of the TMJ with an abscess formation penetrating into the epidural space. Immediate drainage and craniotomy were performed. Under intravenous antibiotics, the patient made a full recovery. The source of infection remained undetermined. To our knowledge, this is the first reported case of septic arthritis of the TMJ spreading into the epidural space.